'More Savage than White Bears': The Diplomatic Etiquette of Revolutionary France. (2nd January 2017) - Frey, Linda; Frey, Marsha
Abstract : The revolutionary leaders in France challenged Europeans' assumption of a common diplomatic culture, of a universal diplomatic language, and most basically, an international diplomatic community. But rather than rejecting the old ways completely, they re-emphasised the importance of ritual and gesture, not just as assertions or reflections of ideology, but as tools in the reconstruction of their world and the diplomatic system. Diplomatic protocol and ceremony became a symbolic battleground on which the struggle between the old and the new order was enacted. This article, based largely on archival material including the private correspondence of many diplomats, notably James Harris, Baron Malmesbury, demonstrates how a new etiquette, both more republican and more militaristic, replaced the old one.